60 years of Human Relations - Loveridge, R; Willman, P; Deery, S (Sage Publications Ltd., 2007)
Human Relations was founded in 1947 as a collaborative transatlantic project between the Tavistock Institute of Human Relations in London and the Research Center for Group Dynamics at the Massachusetts Institute of Technology. Its objective was to encourage theoretical and methodological contributions to the social sciences and to promote their practical application to solve community problems. This article traces the development and evolution of the journal and seeks to assess its contribution to social science research. It examines the intellectual role of the Tavistock Institute and the tensions and pressures that the journal has faced over the past 60 years as it has sought to fulfil its mission and achieve its academic goals.